Ranking Hits From Saturation Transfer Difference Nuclear Magnetic Resonance–Based Fragment Screening - Aretz, Jonas; Rademacher, Christoph (Frontiers in Chemistry, 2019)
Fragment-based screening is an established route to identify low molecular weight molecules to generate high affinity inhibitors in drug discovery. The affinities of these early hits from fragment screenings require highly sensitive biophysical screening technique. Saturation transfer difference (STD) NMR is one of the most popular methods owing to its high sensitivity for low affinity ligands. It would be highly beneficial if rank-ordering of hits according to their affinity from an initial or counter-screen could be performed - a selection criterion found in the literature. We applied CORCEMA-ST calculations to predict STD NMR results from a large set of fragment/receptor pairs to investigate the boundaries under which the assumption holds true that a high STD effect can be applied to select for higher affinity fragments. Overall, we come to the conclusion that this assumption is invalid.